Studi Kasus Boiler CFB: Kenaikan Temperatur Bed - Abuhanif, Hanan Riswandha; Firdaus, Nofirman; ., Hendri; Rusjdi, Halim (KILAT, 2022)
The bed material in the furnace in a PLTU has a temperature rise that is too high. The reason is that the size of the coal is too large and there are many clogged nozzles. The aims of this research is to investigate the increase in boiler bed temperature of circulating fluidized bed (CFB) boiler which cause negative effects on boiler performance. The research method used was a case study. The result shows that the main causes of high bed temperature is the clogged nozzle and deformation. In addition, operating parameter of the boiler can be used to detect fault. The increase of bed temperature lead to high flue gas temperature and lower efficiency of boiler. To overcome this issue, it is suggested that the nozzles need to be modified according to the operating condition of the boiler.